Genomic scans for selection and runs of homozygosity in southern Italian turkey populations - Medhat S. Saleh; Vincenzo Landi; Martijn F.L. Derks; Gerardo Centoducati; Martien A.M. Groenen; Pasquale De Palo; Elena Ciani; Nicola Pugliese; Elena Circella; Antonio Camarda (Poultry Science)
Basilicata and Apulian (BAS-APU) turkeys, a native population in the Basilicata and Puglia regions of southern Italy, are known for their high meat quality and tolerance to local conditions. Understanding the genomic patterns of BAS-APU turkeys is critical for effective breeding and preservation strategies. In this study, we characterized runs of homozygosity (ROH), and selection signatures using the integrated haplotype score (iHS) and ROH approaches. A total of 73 BAS-APU turkeys from five populations were sequenced (12X). The inbreeding coefficients based on ROH ranged from 0.177 to 0.405. A total of 120,956 ROH were detected in BAS-APU populations. We identified 27 genomic regions that harbor 61 candidate genes in ROH islands in which single nucleotide polymorphisms (SNPs) occur in more than 90 % of individuals. In addition, we detected 608 genomic regions under positive selection using the iHS method being 104, 98, 130, 102, and 174 for BAS, APU_C, APU_M, APU_PN, and APU_PS, respectively. For both methods, most of the genes within these regions are related to production performance, reproduction, immune responses, and adaptation. This study contributes significantly to our understanding of the genetic makeup of native turkey populations in southern Italy. The identified genes under selection can aid future breeding and conservations programs for southern Italian native turkeys. The results of inbreeding levels, especially in the absence of complete pedigrees or when only a few samples are available, which is often the case for local breeds, will help to avoid genetic relatedness in the mating plan in breeding and conservation plans for BAS-APU populations. Also, the detected genes in the selective sweep regions could be used as a marker-assisted selection to improve productive traits and adaptation of BAS-APU local populations.